2021
DOI: 10.1039/d1cp00321f
|View full text |Cite
|
Sign up to set email alerts
|

A novel shift in the glass transition temperature of polymer nanocomposites: a molecular dynamics simulation study

Abstract: The effect of nanoparticles on the glass transition temperature, Tg, of polymer nanocomposites is studied by using molecular dynamics simulations. Tg is estimated from the variation of system volume with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…With an increase in the volume fraction of NPs, a decrease in Tg is observed first and then an increase in Tg. The nonlinear dependence of Tg and thermal conductivity of the nanocomposite on the dopant concentration was found by us in previous studies and is described in the literature [71,72]. The nonlinear character of the dependence of the Tg of the nanocomposite on the dopant concentration was also found in mathematical modeling [73].…”
Section: Discussionmentioning
confidence: 56%
“…With an increase in the volume fraction of NPs, a decrease in Tg is observed first and then an increase in Tg. The nonlinear dependence of Tg and thermal conductivity of the nanocomposite on the dopant concentration was found by us in previous studies and is described in the literature [71,72]. The nonlinear character of the dependence of the Tg of the nanocomposite on the dopant concentration was also found in mathematical modeling [73].…”
Section: Discussionmentioning
confidence: 56%
“…Earlier reports on DNT/polymer systems indicated that the attractive force between the polymer and DNT reduced the sample volume (passivation effect), while the repulsive force between DNTs increased the sample volume (activation effect). 66 With the increase of DNT, the passivation effect between DNTs became stronger than the activation effect between DNTs and polymer, leading to a parabolic relationship. In our work, there is localized aggregation of DNT, which leads to the marginal volume change of the bituminous binder, resulting in a weak relationship.…”
Section: Resultsmentioning
confidence: 99%
“…25,27 However, for semi-dilute polymer solutions, both experiments and simulations showed that the concentration of NPs did not change the normal diffusion properties of polymers, 20,30 although the diffusion coefficient was dependent on the concentration of NPs. 31,41 To understand the transition from subdiffusion to normal diffusion of polymer chains, it is therefore interesting to investigate the transition concentration of polymer chains at different concentrations of NPs. In this section, the size of NPs σ n = 5 is fixed.…”
Section: Resultsmentioning
confidence: 99%